Clean‐label bread: Using hard red spring wheat to replace dough improvers in whole wheat bread. Issue 12 (15th September 2020) - Simsek, Senay
Abstract: Clean‐label foods are increasing in popularity, and clean‐label breads are needed since bread formulations often contain several dough/bread improvers that are not considered clean‐label by consumers. This research investigated the use of hard red spring (HRS) wheat as an alternative ingredient to improve whole wheat bread quality, while maintaining a clean‐label. Hard red winter (HRW) whole wheat flour was blended with three levels of three different HRS whole wheat flours or with eight different dough conditioners. Each treatment was evaluated for dough, and baking qualities by AACC International Approved Methods. Increasing the percentage of HRS flour significantly ( p  < .05) increased the Farinograph water absorption and stability. Bread‐specific volume significantly ( p  < .05) increased with increasing percentages of HRS flour. Bread firmness decreased with increasing percentages of HRS flour. Overall, the HRS blends produced dough and bread quality parameters that were equal to or better than the additives. Practical applications: The main application of this research is to provide an alternative to common bread additives to develop clean‐label whole wheat bread products. This research shows that many bread additives that are no longer accepted by consumers can be replaced by adding wholemeal hard red spring wheat with good protein quality to whole wheat bread. The quality of clean‐label whole wheat breads can be brought to the same level, or better, as traditional whole wheat breads containing dough improver ingredients.